Analisis Keselarasan Pemanfaatan Ruang dengan Rencana Pola Ruang dan Pengendaliannya di Kota Jakarta Timur - Andy Purwa Sejati; Santun R.P Sitorus; Janthy T Hidayat (TATALOKA, 2020)
The rapid development in East Jakarta City has led to increased  land  requirements and causes unalignment of land use. Research objective are to analyze the alignment of spatial usage with the spatial plan and its control in East Jakarta City. The research methods used are spatial analysis based on image interpretation and Geographic Information System, descriptive statistic for seeking influence factors, description analysis for spatial control usage and its guidance. Results analysis for 6 (six) existing land use showed that alignment of existing land use has area of 12.430,5 ha or 76.5 % and unalignment of existing land use has area 3.812,7 ha or 23.5%. Factors that influence unalignment of existing land use, namely economic needs, housing needs, distance from the economic center, distance from the road, lack of socialization to the community, population density and the presence of public facilities. Analysis of the implementation of spatial usage control shows that the East Jakarta City Government has implemented 4 spatial usage control instruments namely the Spatial Detail Plan along with its Zoning Regulations, licensing, providing incentives and disincentives and sanctions but the implementation is still considered not maximally. Directives for improving spatial usage are carried out by maximizing and improving the implementation of four instruments for controlling spatial usage.